MATHEMATIC-PHYSICAL MODEL OF DIMENSIONING SYSTEM IN THE PROPAGATION OF MICROWAVE "WAVEGUIDE-SLUDGE“ FROM WASTEWATER TREATMENT PLANTS - Riti-Mihoc, Emilian-Narcis; Riti-Mihoc, Emil; Porcar, Dan (European Scientific Journal, ESJ, 2013)
This paper presents a physico-mathematical model sizing system microwave field propagation through a waveguide of the waveguide composed of a rectangular section and a pyramidal funnel section rectangular variable distribution. This model was adapted to the conditions of "waveguidepond sludge bed" treaty. The system is to define parameters and propagation equations for adaptation.